Huge Ovarian Cyst Imitating Pregnancy - Bajracharya, Nishma; Karki, Aruna; Dangal, Ganesh; Pradhan, Hema; Shrestha, Ranjana; Bhattachan, Kabin; Paudel, Rekha (Nepal Journal of Obstetrics and Gynaecology, 2018)
Ovarian cysts are common findings in females of reproductive age. Mostly, they are non-neoplastic and hormonally dependent as follicular, simple, and corpus luteum cysts. Ovarian cysts are rarely grown to reach huge size without raising any symptoms. Most of the cases that have huge cysts present with pressure symptoms over the genitourinary system leading to urinary complaints or the respiratory system lead to respiratory embarrassment. Dermoid cysts account for 10–20% of all ovarian neoplasms. They are common in young women, especially at the age of 30 years.In most of cases, they are asymptomatic and can be discovered accidentally on clinical examination or ultrasonographic scan. They are usually indolent tumors with very slow rate of growth about 1.8 mm per year. Giant dermoid cysts have been infrequently reported in the literature. This is a case report of huge dermoid cyst weighing 25 kgs in a 42-year old perimenopausal lady that remained relatively asymptomatic. She underwent Laparotomy with ovarian cystectomy.